IMPLEMENTASI PENDAFTARAN SERTIPIKAT HAK MILIK ATAS TANAH DALAM PEMBAGIAN WARIS DAN PERMASALAHANNYA DI KANTOR PERTANAHAN KOTA SEMARANG - Musta’in Musta’in; Sukarmi Sukarmi (Program Magister (S2) Kenotariatan, Fakultas Hukum, Universitas Islam Sultan Agung, 2017)
The relationship between man and the land is so close that the land as a human place to live and continue his life. Land issues are also related to the granting of land rights such as inheritance. Judicially, the acquisition of rights due to inheritance is the acquisition of rights to land and or building by the heirs of the testator, which is applicable after the heirs pass away. Principally, when the heir dies, there has been a transfer of rights from the heirs to the heirs.In the transfer of ownership of the land mentioned above, of course, in making the aktanya different, from some reasons mentioned above, the authors are interested to develop a research with Title: registration certificate of ownership of land in the distribution of inheritance and problems at the Office of Land City of Semarang covering : How is the registration of the land ownership certificate in the division of inheritance in the Land Office of Semarang City, what is the legal effect if the inheritance is not made in the Land Office, and what if there is a heir disputed land dispute is sold but one of the heirs is not Signed a deed of sale and did not provide data. The purpose of the study To analyze and review the registration of land ownership certificates in the distribution of inheritance, to examine and analyze the legal consequences if the land of inheritance divestment is not made in a certificate, and to analyze and assess if there is an inheritance dispute of land which has been certified is sold but one of the heirs is not Signed a deed of sale and did not provide data.The research method used is juridical empirical. The results of this study can be concluded that, the guarantee of legal certainty in the field of land, with the existence of written, complete, and clear legal tools are carried out consistently. In addition, in the face of concrete cases it is also necessary that the registration of land that can provide legal certainty of the land for the right holders to facilitate prove it.Keywords: Registration, certificates, property rights, inheritance.